Design and content validation of the Oral Hygiene Habits Scale. - Norma Idalia Rodríguez; José Moral (Universidad de Concepción., 2016)
The presence of dental plaque is associated with deterioration of oral health, tooth decay, gingivitis and periodontal disease. The study of content validity of a new instrument aims to determine whether the items included in the measuring instrument are representative of the assessed construct. The objective of this research was to design and validate the content of an oral hygiene habits scale. A Likert-like scale, named Oral Hygiene Habits Scale (OHHS), containing 10 items and five response options on frequency of behavior, was developed to assess the dimensions of toothbrushing and flossing. Six experts were recruited for the study. They were asked to conduct their evaluations individually. Four characteristics (adequacy, clarity, consistency and relevance) were evaluated for each item, using an assessment scale of four ordinal values (from 1="does not meet the criteria" to 4="high level of compliance"). Data were analyzed using the binomial test, Kendall's W and Fleiss's Kappa coefficient. The judges mostly indicated a high level of compliance with the characteristics evaluated for each item and their judgments were consistent with one another. It is concluded that the OHHS composed of 10 items showed content validity. Further studies are suggested to determine its reliability and construct validity.